Multi-objective design optimization on building integrated photovoltaic with Trombe wall and phase change material based on life cycle cost and thermal comfort. (August 2021) - Lin, Yaolin; Zhong, Shengli; Yang, Wei; Hao, Xiaoli; Li, Chun-Qing
Abstract: This study performed design optimization on a building with integrated photovoltaic, Trombe wall and phase change material based on building life cycle cost (LCC) and indoor thermal comfort. A total of thirty-four design variables were considered as the optimization variables. The optimization process consists of four steps. Firstly, Monte Carlo Method was used to generate a set of design samples, and the LCC and indoor discomfort degree hour were obtained through computer simulation. Secondly, stepwise linear regression (SLR) and artificial neural network (ANN) models were developed as the prediction models. ANN models exhibited better prediction performance with errors of less than 6%. Thirdly, six optimization algorithms were selected to couple with the ANN models for design optimization and the Strength Pareto Evolutionary Algorithm II (SPEA II) presented the best performance. Finally, optimization with different groups of design variables were conducted by using the SPEA II algorithm. Compared with the reference building, the optimal solutions reduce life cycle cost up to 45.51% and improve thermal comfort level up to 43.81%. The recommended heating and cooling temperature setpoint is around 18 °C and 24 °C, respectively. The PCM type convergence value is BioPCM M182/Q21, and the east and west window-to-wall ratios are around 10%.